THE EFFECT OF WORK ENVIRONMENT, WORK MOTIVATION AND INTERNAL COMMUNICATION ON EMPLOYEE JOB SATISFACTION AT PT TRUBA JAGA CITA SITE SOROWAKO - Kristina Seni; M. Rudi Irwansyah; Komang Krisna Heryanda (RADJA PUBLIKA, 2026)
This study aims to determine and analyze: (1) the influence of the work environment on employee job satisfaction, (2) the influence of work motivation on employee job satisfaction, (3) the influence of internal communication on employee job satisfaction, (4) the influence of the work environment, work motivation, and internal communication simultaneously on employee job satisfaction at PT Truba Jaga Cita Site Sorowako. The research method used is quantitative, where the population is 30 employees at PT Truba Jaga Cita Site Sorowako. The sample determination uses a saturated sample technique where all members of the population are used as samples. This study was designed in the form of explanatory research . Data were collected using questionnaires and analyzed using SEM-PLS analysis. The results of the study indicate that the work environment has a significant impact on increasing employee satisfaction. Work motivation has a positive and significant effect on job satisfaction. There is a significant influence of internal communication in increasing employee job satisfaction.